Exploring how the Game Master-Player relationship influences narrative in video games - Abel João Gavinho Vaz Tavares Neto (2016)
The purpose of this research is to explore how the relationship between game participants that assume the role of Game Master and those that have that of Player influences narrative in videogames. This relationship, barely explored in computer games, has existed in board games for decades, one of the first examples being Dungeons & Dragons, in which a game participant acts both as a referee and as a storyteller, controlling all aspects of the game, except for the actions of the players. Through the development of a game prototype, we found that there's value in including this asymmetry in computer games, and evaluated its viability and benefits/disadvantages.